Potential complementarity between forest carbon sequestration incentives and biomass energy expansion. (March 2019) - Baker, J.S.; Wade, C.M.; Sohngen, B.L.; Ohrel, S.; Fawcett, A.A.
Abstract: There is a growing literature on the potential contributions the global forest sector could make toward long-term climate action goals through increased carbon sequestration and the provision of biomass for energy generation. However, little work to date has explored possible interactions between carbon sequestration incentives and bioenergy expansion policies in forestry. This study develops a simple conceptual model for evaluating whether carbon sequestration and biomass energy policies are carbon complements or substitutes. Then, we apply a dynamic structural model of the global forest sector to assess terrestrial carbon changes under different combinations of carbon sequestration price incentives and forest bioenergy expansion. Our results show that forest bioenergy expansion can complement carbon sequestration policies in the near- and medium-term, reducing marginal abatement costs and increasing mitigation potential. By the end of the century these policies become substitutes, with forest bioenergy expansion increasing the costs of carbon sequestration. This switch is driven by relatively high demand and price growth for pulpwood under scenarios with forest bioenergy expansion, which incentivizes management changes in the near- and medium-term that are carbon beneficial (e.g., afforestation and intensive margin shifts), but requires sustained increases in pulpwood harvest levels over the long-term. Highlights: Forests can contribute to climate mitigation goals. Forest bioenergy and carbon sequestration can be complementary. The level of complementarity could diminish over time. Interactions between policy drivers and pulpwood/sawtimber markets are a key driver.